Thanatos in Shakespeare’s Hamlet, Homer and Barker’s Achilles, Barnes and Saunders: Warding off Death before Release into the Unknown - ALBAN, GILLIAN MARY ELIZABETH (Çankaya University, 2021)
This paper offers an existential approach to writers’ responses to death, evaluatingtheir different views regarding our ultimate destiny, Thanatos. It considers thedeliberations of Shakespeare’s Hamlet, the archetypal death-ponderer, and Homer’sAchilles, approaching our own time through contemporaries like Julian Barnes,George Saunders and Pat Barker. These writings spanning hundreds of yearsdemonstrate our desire to evade or control death, while anticipating ultimatejudgment for behaviour in this life, before loosening our attachment to life inaccepting our final fate. We watch Hamlet’s concern for his father’s ghost tortured inpurgatory and his wish for revenge, as it became surpassed by Hamlet’sinterrogations concerning his own mortality, still obsessed by death, to which forcehe finally surrenders. While Achilles had initially embraced a gloriously heroic,youthful death, Homer subsequently shows him mourning the loss of his life in Hades;Pat Barker shows Achilles as reconciled to death, even while attached to life inconsidering his child’s future. The contemporary George Saunders presents Lincoln’syoung son caught in a liminal bardo of the dead, who are trapped in attachment totheir mortal state, while Willie is enabled to transition to his final state of possiblejudgment and closure. Julian Barnes’ wish-fulfilment dream or desire of heaven offersthis ideal as a debased, corporeal paradise, leaving his character longing for meaning,even while trapped in the limitations of his own personality. Visions and dreams fromHomer and Shakespeare onwards offer cryptic clues regarding unknown futurestates. These literary reflections through disparate eras indicate the humanaspiration to evade death and whatever lies beyond it, while often positing a finalsurrender to death, alongside a wish for it to make sense of life through karmicresolution.
Shakespeare’in Hamlet, Homer ve Barker’in Achilles’den, Barnes ve Saunders’e: Ölümden Kaçmak, Sonunda Bilinmeyen’e Yenik Düşmek
Keywords: Death; Bardo; Purgatory; Judgment; Resolution; Nothing